EVALUATION OF ETHANOL EXTRACT OF TARO LEAVES (COLOCASIA GIGANTEA) AS MALNUTRITION THERAPY: IN VIVO TEST - HUSNA, ADLINA KARIMINA NURUL; WIDYAWATI, TRI; ANGGRAINI, DWI RITA (International Journal of Applied Pharmaceutics, 2025)
Objective: Skeletal muscle mass and small intestine function are two areas of the body that are severely impacted by malnutrition. Many communities rely on Colocasia gigantea (Talas Padang) as a common food source to address this nutritional challenge. Methods: The design of this study included male white rats of Wistar strain 6-8 w old induced into 25 malnourished model mice with a Post-test Only Control Group involving 5 experimental groups. Group K1 (normal control) was given normal diet for 56 d, while Group K2 (positive control) was given a Low Protein Diet (LPD) for 14 d followed by a normal diet for 42 d. As for Groups K3, K4, and K5 received 14 d of LPD followed by a normal diet combined with Ethanol Extract of Taro Leaves (EETL) at doses of 100, 200, and 400 mg/kgBW orally for 42 d, respectively. The expression of AMPK-α1 in soleus muscle and PepT1 expression in small intestine tissues were examined with immunohistochemistry. The analysis was done using Shapiro-Wilk test for normality, Levene's for homogeneity, one-way ANOVA for parametric data, and Kruskal-Wallis non-parametric test for comparison. Post-hoc analysis was carried out by Mann-Whitney test. Results: The administration of ethanol extract of taro leaves (EETL) appeared to affect the expression of AMPK-α1 and PepT1 in Wistar rats. While group K4 (200 mg/kgBW) showed the highest AMPK-α1 expression (median: 18, IQR: 9.00), no statistically significant differences were observed among the groups (p>0.05). For PepT1 expression, group K4 also demonstrated elevated and more consistent values (median: 15, IQR: 3.00), with a statistically significant difference between treatment groups (p = 0.028). Conclusion: Although the expression of AMPK-α1 did not increase statistically, the treated rats showed an increase in expression, which was usually seen in association with the improved PepT1 expression in the treated animals. Therefore, EETL at a dose of 200 mg/kgBW is potentially beneficial in modulating the malnutrition-relevant parameters, albeit just showing trends for increased expression at that dose. Further studies should continue to be done to confirm the effects and mechanisms behind them.